2003
DOI: 10.1002/adma.200390087
|View full text |Cite
|
Sign up to set email alerts
|

One‐Dimensional Nanostructures: Synthesis, Characterization, and Applications

Abstract: This article provides a comprehensive review of current research activities that concentrate on one‐dimensional (1D) nanostructures—wires, rods, belts, and tubes—whose lateral dimensions fall anywhere in the range of 1 to 100 nm. We devote the most attention to 1D nanostructures that have been synthesized in relatively copious quantities using chemical methods. We begin this article with an overview of synthetic strategies that have been exploited to achieve 1D growth. We then elaborate on these approaches in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
5,458
3
55

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8,425 publications
(5,564 citation statements)
references
References 376 publications
48
5,458
3
55
Order By: Relevance
“…119 The anisotropic morphology of preformed seeds could lead to the formation of branched Pt nanostructures through nonsymmetrical growth. 15 Using preformed nanostructures as seeds, well-defined core-shell structures, nanowires and nanotubes were synthesized. 16,96,98 Mahmoud et al 47 employed tetrahedral Pt as seeds to fabricate star-like Pt nanostructures with up to thirty arms, as shown in Fig.…”
Section: Developments Of the Synthetic Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…119 The anisotropic morphology of preformed seeds could lead to the formation of branched Pt nanostructures through nonsymmetrical growth. 15 Using preformed nanostructures as seeds, well-defined core-shell structures, nanowires and nanotubes were synthesized. 16,96,98 Mahmoud et al 47 employed tetrahedral Pt as seeds to fabricate star-like Pt nanostructures with up to thirty arms, as shown in Fig.…”
Section: Developments Of the Synthetic Methodsmentioning
confidence: 99%
“…51 Furthermore, some nanostructures enclosed within high-index facets could contain more unsaturated atomic steps, edges and kinks, which are believed to be more catalytically active than the commonly formed nanostructures within low-index facets. 15,37,52 Tian et al 53 reported Pt tetrahexahedra with exposed high-index planes (e.g. {730}, {210} and {520} facets), which exhibited 2-4 times more efficiency per unit surface area for ethanol oxidation compared to a commercially available Pt/C catalyst, that is usually enclosed with low-index planes such as {111} and {100}.…”
Section: Current Status-geometric and Compositional Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Owning to these advanced properties as well as abundance of carbon on the earth, CNT is an important candidate to build flexible electronics. [25][26][27] However, it is seldom regarded as a TE material due to its poor Seebeck coefficient (< 60 μV/K) 28 and high thermal conductivity of a single tube (~ 250-10000 Wm -1 K -1 for single tube or aligned arrays) [29][30][31] . It has been reported that low thermal conductivities can be obtained in CNTs/conductive polymer composites and processed tubes.…”
Section: Introductionmentioning
confidence: 99%